1995
DOI: 10.1161/01.hyp.26.5.801
|View full text |Cite
|
Sign up to set email alerts
|

Target Organ Status and Serum Lipids in Patients With White Coat Hypertension

Abstract: Target organ status and serum lipids were investigated in white coat hypertension in comparison with sustained hypertension and normotension. We selected three groups balanced for sex, age, body mass index, and smoking habit: 50 sustained hypertensives (clinical hypertension and 24-hour ambulatory blood pressure > 135/85 mm Hg, a cutoff limit obtained from a normotensive population), 25 white coat hypertensives (clinical hypertension and 24-hour ambulatory blood pressure < 135/85 mm Hg), and normotensives. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 49 publications
4
71
1
1
Order By: Relevance
“…13 If this was the case, then one would expect that differences between normo-and white coat hypertensives with regard to target organ changes would disappear when the groups are further controlled for 24-h BP. Indeed, two such studies, 9,10 comparing left ventricular mass between normotensive and WCH groups, where 24-h BP was comparable across the two groups, showed no difference in structural heart changes. On the other hand, Glen et al 3 in a similarly designed study, with BP equivalence between the normal and WCH groups, showed evidence of functional cardiac derangement in the WCH group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 If this was the case, then one would expect that differences between normo-and white coat hypertensives with regard to target organ changes would disappear when the groups are further controlled for 24-h BP. Indeed, two such studies, 9,10 comparing left ventricular mass between normotensive and WCH groups, where 24-h BP was comparable across the two groups, showed no difference in structural heart changes. On the other hand, Glen et al 3 in a similarly designed study, with BP equivalence between the normal and WCH groups, showed evidence of functional cardiac derangement in the WCH group.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies looking at evidence of target organ damage have given equivocal results; left ventricular hypertrophy and renal dysfunction have both been described as occurring in association with WCH, [3][4][5][6][7][8] while other studies have not documented an association. [9][10][11][12] These studies have largely shown significantly higher mean BP in the WCH group, and it may be that the documented elevation of cardiac and renal indices of end-organ involvement found Conclusion: White coat hypertension is indeed associated with a larger left ventricular muscle mass than normotensives and these changes are independent of the actual 24-h BP load, and may reflect increased BP lability, sympathetic nervous system derangement, or a genetic propensity in people with white coat hypertension to stress-related hypertensive reactions, as part of a pre-hypertensive state.…”
Section: Introductionmentioning
confidence: 99%
“…Many, but not all, of these studies have demonstrated increased LVMI in WCH subjects, with LVMI intermediate between that of subjects with normotension and those with sustained hypertension. [2][3][4][5][6][7][8][9][10][11][12][13] In addition, a recent study suggests that the long-term incidence of stroke may be elevated in adults with WCH. 14 Little is known about the clinical significance and natural history of WCH in children.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] The lack of an agreed definition for WCH further adds to the confusion. Furthermore, interpretation of these studies has been made more difficult as many are not controlled for the level of ambulatory BP.…”
Section: Association With Target Organ Damagementioning
confidence: 99%